TINDAKAN EKSPLORASI DAN EKSPLOITASI GAS OLEH ISRAEL BERDASARKAN UNITED NATIONS CONVENTION ON THE LAW OF THE SEA 1982: Gas Exploration And Exploitation Measures By Israel Under United Nations Convention On The Law Of The Sea 1982 - Galih Bima Wasena; Yulia Fitriliani (Faculty of Law, Universitas Trisakti, 2024)
The dispute over determining maritime boundaries in the East Mediterranean Sea between Lebanon and Israel, which contains natural gas reserves, where Israel carried out gas exploration and exploitation actions in the disputed area, prompted this research to answer the issue of whether Israel's actions constitute a violation of UNCLOS 1982 and how to resolve the dispute according to UNCLOS 1982. This research uses a normative method, where secondary data is processed qualitatively and conclusions are drawn deductively. The research results illustrate that Israel's exploration and exploitation actions in the disputed area of the Eastern Mediterranean Sea have violated UNCLOS 1982, Article 74 paragraph (1), Article 77 paragraphs (1) and (2). Then the resolution of the territorial dispute was carried out by the two countries as a voluntary dispute resolution, which is also stated in UNCLOS 1982 and the UN Charter. Dispute resolution by mediation where the mediator is the United States. Then, Israel and Lebanon agreed on the results of the mediation, this settlement was in accordance with the UN Charter Article 33 paragraph (1).